Numerical Study of Tsunami Generation Mechanism - Alwafi Pujiraharjo (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2010)
Tsunami can be gererated by seafloor deformation (fault), under water or sub-marine landslides, under water explosions, and asteroids impact. However, most of tsunami cases are generated by fault. Numerical study of tsunami generation mechanisms are investigated. Tsunami generation by faults are studied and focused on the effects of dispersion and nonlinearity on tsunami generation. Simulations included tsunami generation at deep, intermediate, and shallow water regions. Numerical simulation showed that at deep and intermediate water region the dispersion effect reduce the generated tsunami profile by shifting the profile into more than one wave while the nonlinearity effect does not important for this case. At shallow water, both dispersion and nonlinearity did not take effect to generated tsunami profile. Durations of seabed movement are also simulated to investigate the effect of fast and slow event generation of tsunami. For fast event tsunami propagation, generated tsunami profiles are similar to the profiles of bottom motion.